The Pengungkapan Informasi Tentang Digitalisasi dan Nilai Perusahaan - Rian Firmansyah; Herlina Helmy (Universitas Negeri Padang, 2023)
The purpose of this study is to find out how the effect of disclosing information about digitalization on company value in the food & beverage sub-sector, the textile & garment sub-sector, and the chemical sub-sector which are listed on the Indonesian stock exchange. This research is included in the type of causality research using a quantitative approach. The data in this study were sourced from company annual reports obtained from the website of the Indonesian stock exchange and the website of each company that was sampled. In testing the hypothesis, this study used panel data regression analysis using Eviews software version 12. Based on tests carried out, the results of this research show that disclosing information about digitalization has no effect on the value of companies in the food & beverage subsector, textile & garment subsector, and chemicals subsector listed on the Indonesian Stock Exchange for the 2019 - 2021 period.